Going down in flames: what proportion of reforested peat swamp forests burn in Southeast Asia? - Zeng, Fan Yi (Nanyang Technological University, 2022)
Tropical peat swamp forests (TPSF) act as significant carbon sinks and provide important ecological and socioeconomic benefits. However, TPSF in Southeast Asia have been facing substantial deforestation and degradation from human activities. Although reforestation of degraded TPSF has been widely promoted, reforestation efforts are greatly hindered by the occurrence of fires. Knowledge on the proportion of reforestation sites lost to fire constitutes a crucial evidence gap, which when addressed can better guide future reforestation efforts. In this paper, locations of reforestation sites across Southeast Asia were combined with remotely-sensed burn data to obtain the proportion of reforestation sites burned from 2001 to 2019, with multiple buffer sizes used in burn detection to account for uncertainties in site area. Burn occurrence, timing, and severity were also analysed for active reforestation versus natural regeneration sites, sites of different LULC types, and drained versus rewetted sites. One-fifth to half of all reforestation sites were found to have burned, and open degraded sites faced a significantly higher probability of burning. 70% to 80% of burned sites experienced fire within the first four years of reforestation, but only 20% of sites had monitoring periods of at least four years to capture potential burns. Results highlight the need for more attention to be placed on post-reforestation monitoring and fire prevention, especially for open degraded sites, to ensure the longevity of peatland restoration efforts.